Reorienting Priorities of Extension and Advisory Services in India during and Post COVID-19 Pandemic: A Review - Chander, Mahesh; Rathod, Prakashkumar (Indian Journal of Extension Education, 2020)
Extension and Advisory Services (EAS) are delivered by millions of extension professionals representing theÂ public, private and civil society located across the globe and have been helping in addressing farmersâ€™ needs over the years, including during COVID-19 pandemic situation. However, public sector has been a major agencyÂ dealing with EAS in India and is facing several challenges and constraints to fulfil the demands of farmers on timely basis. The challenge today is to change the organizational culture to incorporate innovation as a core value and to institutionalize the emerging paradigms. Further, different strategies and measures need to beÂ taken to ensure timely and quality EAS by reorienting extension priorities in such emergency situations andÂ later too. In this context, an effort to review the extension mechanism across India and also has focused on reorienting extension priorities post COVID-19 scenario. The study has highlighted on strengthening extension and feedback mechanism, improving research-extension linkages, capacity building, public-private partnership (PPP), developing infrastructure, mass media support and use of Information and Communication TechnologiesÂ (ICTs) etc. to improve the efficiency as the time demands. The paper concludes that reorienting extension priorities is very essential with a vast network of various stakeholders by adapting effective approaches like utilization of social media, human resource development, PPP, farmer groups etc. during and post pandemic scenario. Further, empirical efforts are also needed to develop reliable, location-specific, participatory, gender-sensitiveÂ and inexpensive extension methodologies and materials to meet the demands during such crisis. Further, developing countries like India have to invest in terms of various resources like financial, humanÂ resource etc. for promoting higher productivity and sustainability through EAS.